Corrosion of Mechanically Alloyed Nanostructured FeAl Intermetallic Powders - A. Torres-Islas; C. Carachure; S. Serna; B. Campillo; G. Rosas (Advances in Materials Science and Engineering)
The corrosion behavior of the Fe40Al60 nanostructured intermetallic composition was studied using electrochemical impedance spectroscopy (EIS) and linear polarization resistance (LPR) techniques with an innovative electrochemical cell arrangement. The Fe40Al60 (% at) intermetallic composition was obtained by mechanical alloying using elemental powders of Fe (99.99%) and Al (99.99%). All electrochemical testing was carried out in Fe40Al60 particles that were in water with different pH values. Temperature and test time were also varied. The experimental data was analyzed as an indicator of the monitoring of the particle corrosion current density icorr. Different oxide types that were formed at surface particle were found. These oxides promote two types of surface corrosion mechanisms: (i) diffusion and (ii) charge transfer mechanisms, which are a function of icorr behavior of the solution, pH, temperature, and test time. The intermetallic was characterized before and after each test by transmission electron microscopy. Furthermore, the results show that at the surface particles uniform corrosion takes place. These results confirm that it is possible to sense the nanoparticle corrosion behavior by EIS and LPR conventional electrochemical techniques.